How God Acts : Creation, Redemption, and Special Divine Action - Edwards, Denis, 1943- (Book collections on Project MUSE., 2010)
From providence and miracles to resurrection and intercessory prayer, Edwards shows how a basically noninterventionist model of divine action does justice to the universe as we know and also to central convictions of Christian faith about the goodness of God, the promises of God, and the fulfillment of creation. Here is wonderfully lucid theology supporting an excitement of how God is at work in the universe.